2017 National Standards for Diabetes Self-Management Education and Support. Issue 1 (February 2019) - Beck, Joni; Greenwood, Deborah A.; Blanton, Lori; Bollinger, Sandra T.; Butcher, Marcene K.; Condon, Jo Ellen; Cypress, Marjorie; Faulkner, Priscilla; Fischl, Amy Hess; Francis, Theresa; Kolb, Leslie E.; Lavin-Tompkins, Jodi M.; et al.
Purpose: The purpose of this study is to review the literature for Diabetes Self-Management Education and Support (DSMES) to ensure the National Standards for DSMES (Standards) align with current evidence-based practices and utilization trends. Methods: The 10 Standards were divided among 20 interdisciplinary workgroup members. Members searched the current research for diabetes education and support, behavioral health, clinical, health care environment, technical, reimbursement, and business practice for the strongest evidence that guided the Standards revision. Results: Diabetes Self-Management Education and Support facilitates the knowledge, skills, and ability necessary for diabetes self-care as well as activities that assist a person in implementing and sustaining the behaviors needed to manage their condition on an ongoing basis. The evidence indicates that health care providers and people affected by diabetes are embracing technology, and this is having a positive impact of DSMES access, utilization, and outcomes. Conclusion: Quality DSMES continues to be a critical element of care for all people with diabetes. The DSMES services must be individualized and guided by the concerns, preferences, and needs of the person affected by diabetes. Even with the abundance of evidence supporting the benefits of DSMES, it continues to be underutilized, but as with other health care services, technology is changing the way DSMES is delivered and utilized with positive outcomes.